Outcome of Older Patients with Acute Neuropsychological Symptoms Not Fulfilling Criteria of Delirium - Zipprich, Hannah M.; Arends, Marie‐Christine; Schumacher, Ulrike; Bahr, Viola; Scherag, André; Kwetkat, Anja; Wedding, Ulrich; Brunkhorst, Frank M.; Witte, Otto W.; Prell, Tino; Redecker, Christoph (Journal of the American Geriatrics Society (JAGS), 2020)
OBJECTIVES Although delirium is often investigated, little is known about the outcomes of patients having acute neuropsychological changes at a single time point without fulfilling the criteria of full delirium. Our aim was to determine point prevalence, predictors, and long‐term outcomes of delirium and acute neuropsychological changes in patients aged 60 years and older across different departments of a university hospital with general inpatient care. DESIGN Prospective observational study. SETTING University hospital excluding psychiatric wards. PARTICIPANTS At baseline, 669 patients were assessed, and follow‐ups occurred at months 6, 12, 18, and 36. MEASUREMENTS Measurements were obtained using the Confusion Assessment Method (CAM), comprehensive geriatric assessment, health‐related quality of life, functional state (month 6), and mortality rates (months 6, 12, 18, and 36). Subjects were classified into (1) patients with delirium according to the CAM, (2) patients with only two positive CAM items (2‐CAM state), and (3) patients without delirium. RESULTS Delirium was present in 10.8% and the 2‐CAM state in an additional 12.7% of patients. Highest prevalence of delirium was observed in medical and surgical intensive care units and neurosurgical wards. Cognitive restrictions, restricted mobility, electrolyte imbalance, the number of medications per day, any fixations, and the presence of a urinary catheter predicted the presence of delirium and 2‐CAM‐state. The mean Karnofsky Performance Score and EuroQol‐5D were comparable between delirium and the 2‐CAM state after 6 months. The 6‐, 12‐, 18‐, and 36‐month mortality rates of patients with delirium and the 2‐CAM state were comparable. The nurses’ evaluation of distinct patients showed high specificity (89%) but low sensitivity (53%) for the detection of delirium in wide‐awake patients. CONCLUSION Patients with an acute change or fluctuation in mental status or inattention with one additional CAM symptom (ie, disorganized thinking or an altered level of consciousness) have a similar risk for a lower quality of life and death as patients with delirium. J Am Geriatr Soc 68:1469‐1475, 2020.